2018
DOI: 10.1590/1413-70542018425011618
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea production and soil chemical attributes after phosphorus and molybdenum fertilization

Abstract: Chickpea is the third most cultivated legume in the world. In Brazil, cropping of this legume is recent and definitions of fertilizer management techniques are scarce. In this study, the objective was to evaluate chickpea (BRS Aleppo) production and soil chemical attributes with and without phosphorus fertilization and leaf-applied molybdenum. A randomized block experimental design was used, with four replications. A 2 x 5 factorial arrangement was used to evaluate production, consisting of two molybdenum fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Likewise, a study on response to P and Mo fertilization under irrigated conditions in chickpea revealed that the P rate increased stem and grain yield. P 2 O 5 of 160 and 200 kg ha −1 had 5.91 (stem dry matter) and 2.71 t ha −1 (grain) yield, consecutively [126]. Such grain yield was considered high against other countries, such as India, Pakistan, and Ethiopia with mean yield of 0.91, 0.47, and 1.91 t ha −1 , sequentially [152,153].…”
Section: Effect Of P Application Rate On Nodulation Growth and Yield Performance Of Chickpeamentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, a study on response to P and Mo fertilization under irrigated conditions in chickpea revealed that the P rate increased stem and grain yield. P 2 O 5 of 160 and 200 kg ha −1 had 5.91 (stem dry matter) and 2.71 t ha −1 (grain) yield, consecutively [126]. Such grain yield was considered high against other countries, such as India, Pakistan, and Ethiopia with mean yield of 0.91, 0.47, and 1.91 t ha −1 , sequentially [152,153].…”
Section: Effect Of P Application Rate On Nodulation Growth and Yield Performance Of Chickpeamentioning
confidence: 96%
“…e demand for P in chickpea is relatively in large amount for growth and has been revealed to improve leaf area, biomass, yield, number and mass of nodule [125]. Several studies have signified the important role of P in the growth and production of chickpea [22,48,126].…”
Section: Effect Of P Application Rate On Nodulation Growth and Yield Performance Of Chickpeamentioning
confidence: 99%
“…The global consumption of chickpea has shown an increase of 14.2% in area and 27.3% in quantity of production since 2010 [2]. The cultivation of chickpea offers various advantages such as adaptability in a wide range of climatic conditions, low cultivation cost, and the enhancement of nitrogen fixation, thus improving soil fertility [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian semi-arid is a favorable region for the cultivation of this legume (Artiaga et al, 2015;Nascimento et al, 2016), with yields above 2,700 kg ha -1 in irrigated systems (Hoskem et al, 2017;Pegoraro et al, 2018;Almeida Neta et al, 2020;Fonseca et al, 2020). However, high chickpea yields depend on a balanced nitrogen supply (N) and the presence of growth-promoting bacteria.…”
Section: Introductionmentioning
confidence: 99%